Representasi Budaya Multikultural dalam Meme di Media Sosial - Firstya Evi Dianastiti; Agnira Rekha; Muhammad Daniel Fahmi Rizal; Anggita Febriana Wati (STKIP Singkawang, 2020)
This study aims to describe the various types of multicultural culture represented in uploading memes on Instagram social media. This research is a qualitative descriptive study. The analysis was carried out using Barthes' semiotic theory. The research data is in the form of meme uploads on Instagram social media with the account names @ mrci.id and @ memecomic.id. Data collection was carried out from May to August 2020. Based on data collection conducted from May to August 2020, nine data were found from the @ mrci.id and @ memecomic.id accounts that represent multicultural culture. Cultural multiculturalism found is cultural representation of (a) Javanese, (b) Padang, (c) Sundanese, (d) with regard to religious holidays, and (e) regarding cycling culture.